Determinants of subdermal contraceptive use among women of reproductive age: A Cross-Sectional Study - Dahniar, Dahniar; Marbun, Uliarta; Purnama Sari, Lili; Irnawati, Irnawati; Kadir, Arisna (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Family planning is a key global public health strategy to reduce maternal morbidity and mortality. The World Health Organization (WHO) reports that millions of women of reproductive age worldwide still have unmet needs for modern contraception, contributing to preventable maternal deaths and adverse reproductive outcomes. Although long-acting reversible contraceptives such as subdermal implants are highly effective (failure rate <1%), their utilization remains lower than short-term methods in many low- and middle-income countries, including Indonesia. Understanding the determinants of implant use is essential to strengthening family planning programs at the primary health care level. Objective: To analyze factors associated with the use of subdermal contraceptives (Alat Kontrasepsi Bawah Kulit/AKBK) among women of reproductive age at Puskesmas Pattingalloang. Research Methodology: An analytic cross-sectional study was conducted among 50 women of reproductive age, selected by simple random sampling, between December 2024 and January 2025. Data were collected using validated structured questionnaires. Descriptive statistics, chi-square tests, and multivariate logistic regression were performed using SPSS version 26. Statistical significance was set at α = 0.05. Results: Good information exposure (AOR = 9.12; 95% CI: 1.78–46.76; p = 0.008), good husband’s support (AOR = 7.45; 95% CI: 1.56–35.58; p = 0.012), good knowledge (AOR = 6.74; 95% CI: 1.38–32.94; p = 0.019), and age 20–30 years (AOR = 5.21; 95% CI: 1.02–26.60; p = 0.047) were independently associated with AKBK use. Parity, education level, and duration of contraceptive use were not significantly associated. Conclusion: Cognitive and relational determinants play a central role in subdermal contraceptive uptake. Strengthening structured counseling, improving information dissemination, and implementing couple-centered family planning interventions are recommended to enhance long-acting contraceptive utilization and improve maternal health outcomes